Guernsey-Crown Dependency of the United Kingdom : Assessment of the Supervision and Regulation of the Financial Sector Volume II-Detailed Assessment of Observance of Standards and Codes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The completion of the detailed assessment serves several purposes. First, it benchmarks the current state of banking supervision, recognizing that there have been extensive changes in the last years. Second, it suggests a number of further improvements or changes. Thus, this report provides a key input for the development of an action plan to move toward full compliance with the Core Principles. The assessment of the effectiveness of banking supervision was based on a review of the legal framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet